هل يدفع الاقتصاد الأزرق إلى تحقيق النمو الاقتصادي؟ قراءة نظرية وتطبيقية في تجربة سنغافورة - بن رمضان أنيسة; بومدين محمد رشيد (جامعة الوادي University of Eloued, 2024)
تحتل سنغافورة مركزا متقدما بين دول العالم إذ أنها أصبحت تمثل قوة لا يستهان بها في الساحتين الاقتصادية والسياسية، بالرغم من كونها أحد الدول الفقيرة من حيث الموارد الطبيعية وبشكل خاص المياه إلا أنها حققت قفزة نوعية في مجال الاقتصاد الأزرق. وبالتالي نحاول في دراستنا هذه تسليط الضوء على الاقتصاد الأزرق الذي تطورت أهميته كنشاط اقتصادي حتى أصبح بمثابة قطاع جديد يضاف إلى القطاعات الاقتصادية الأخرى لأي دولة، مع قراءة في تجربة سنغافورة حيث أصبح هذا القطاع يؤدي دورا كبيرا في تطور نشاطها الاقتصادي حيث أدى الاستثمار المكثف في تكنولوجيا المياه إلى تحقيق احتياجاتها من المياه العذبة والوفرة فيها، والنشاط التجاري والذي تمثل بشكل خاص في تصدير التكنولوجيا الحديثة لمعالجة المياه، مما انعكس بالإيجاب على مسار التنمية الاقتصادية. Singapore occupies an advanced position among the countries of the world, as it represents an economic and political power, Although Singapore's one of the poor countries in terms of natural resources, especially water. In this study we try to shed light on the blue economy, whose importance has evolved as an economic activity, has become a new sector added to the other economic sectors of any country, with a reading in, however, it has made a quantum leap in the field of Blue economy. This sector is playing a major role in the development of Singapore’s economic, heavy investment in water technology has led to the realization of its fresh water needs and savings, and commercial activity, which is particularly represented in the export of modern water treatment technology NEWater, which reflected positively on the path of economic development.
Does the blue economy lead to economic growth? Insights from Singapore Conceptual and Empirical
Keywords: الاقتصاد الأزرق; سنغافورة; النمو الاقتصادي; تحلية المياه; المياه الرمادية; Blue economy; Singapore; economic growth; desalination; NEWater